The Effect of Urban Poverty Reduction Programs on Community Welfare: A Comparative Study Between Jakarta and Surabaya - Aziz, Abdul; Jamila (Generasi Sains Indonesia, 2025)
Urban poverty remains a major concern in Indonesia as rapid urbanization continues to widen social and economic disparities. This study investigates how urban poverty reduction programs influence community welfare through a comparative analysis of Jakarta and Surabaya. A mixed-methods approach is applied by integrating quantitative household survey data with qualitative information from interviews and focus group discussions. Welfare is evaluated across income, access to education and health, and subjective well-being. The results show that poverty reduction programs have a significant positive impact in both cities but with varying intensity. In Jakarta, participants gained higher incomes and improved access to essential services, supported by stronger program integration. Beneficiaries also reported greater satisfaction and a stronger sense of social inclusion. In contrast, Surabaya showed positive yet moderate effects as programs reduced vulnerability but did not substantially improve income or long-term well-being. The findings highlight the effectiveness of multidimensional interventions in improving urban welfare while emphasizing that local institutional capacity and context-sensitive design are key to achieving equitable and sustainable outcomes.